Studi Kepustakaan Pengendalian Infeksi Soil Transmitted Helminth Pada Ruminansia Di Lahan Kering Nusa Tenggara Timur Secara Kimia Dan Non-Kimia - Ayu Yuliatri Manafe; Meity M Laut; Aji Winarso (Jurnal Veteriner Nusantara, 2023)
Soil Transmitted Helminth (STH) is an intestinal nematode which in its life cycle requires soil for the maturation process. STH infection is classified as neglected disease, which is an infection that is not noticed and is chronic in nature because it does not cause typical clinical symptoms and the effects are only seen in the long term. The purpose of this study was to determine chemical and non-chemical control of STH infection on ruminants in dry land of NTT. The method used is a qualitative descriptive method with a literature study approach. Based on the results of the study, it was found that the chemical control of STH infection on ruminants in the dry land of NTT is from the benzimidazole group because it is easy to obtain, easy to apply and has good effectiveness, some of which are albendazole, mebendazole, levamisole, piperazine, pyrantel pamoate, and tiabendazole. Meanwhile, non-chemical effective control of STH infection can use several types of plants, including Putri malu extract (Mimosa pudica Linn.), katuk leaf extract, basil leaf extract (Ocimum americanum Linn.), soursop leaf extract (Annona muricata L.), alamanda leaf extract (Allamanda cathartica L.), mango arumanis (mangifera indica L.), and moringa leaf (Moringaoleifera L.) which have been studied contain chemical compounds that are beneficial such as anthelmintics, namely saponins, mimosin and tannins.